A large area (70 cm2) monolithic perovskite solar module with a high efficiency and stability. Issue 12 (17th November 2016) - Priyadarshi, Anish; Haur, Lew Jia; Murray, Paul; Fu, Dongchuan; Kulkarni, Sneha; Xing, Guichuan; Sum, Tze Chien; Mathews, Nripan; Mhaisalkar, Subodh G.
Abstract : A large area and highly stable perovskite solar module (10 cm × 10 cm, active area ∼70 cm 2 ) is demonstrated using low cost processing methods and materials. Abstract : Monolithic perovskite modules with active areas of 31 cm 2 and 70 cm 2 and with power conversion efficiencies (PCE) of 10.46% and 10.74%, respectively, were fabricated using scalable printing processes. An ambient stability of more than 2000 h with less than a 5% reduction in efficiency is demonstrated. The electrical quality of the mesoscopic hole transporter and its facilitation of efficient infiltration is paramount.